Zach gets some exercise - Sarah, Duchess of York, 1959-; Cunliffe, Ian (New York : Sterling Children's Books, 2011)
Zach likes computers, books, and television much more than playing outside, but when he makes friends with the new boy next door, he learns to enjoy being active.
School Library Journal
School Library Journal, August 2011
2.8
K-3
K-3
Keywords: Exercise -- Juvenile fiction; Outdoor recreation -- Juvenile fiction; Play -- Juvenile fiction; Exercise -- Fiction; Outdoor recreation -- Fiction; Play -- Fiction; Exercise -- Fiction; Outdoor recreation -- Fiction; Play -- Fiction; Picture books for children